What do we do with myelomeningocele? Multicentric survey - de Arimateia Silva, José; Bottan, Juan; Dech, Gastón; Figueroa, Exequiel; Giraudo, Pablo; Gorga, Agustina; Lamas, Esteban; Ledesma, José Luis; Longhino, Ariel; Morsucci, Edgardo; Sosa, Fidel; Sosa Medina, Enrique; et al. (Revista Argentina de Neurocirugía, 2025)
Background: myelomeningocele (MM) is a well-known pathology on which there are few studies at the national level.Objectives: to survey the neurosurgical management of the treatment of myelomeningocele and associated entities.Methods: retrospective and observational study of the medical records of 475 patients operated on in the last 5 years. The questionnaire was sent to 18 members of the Argentine Society of Pediatric Neurosurgery. Frequents complications, appearance and treatment of hydrocephalus, behavior in the face of Chiari malformation, syringomyelia and transition in adulthood were recorded. The calculation of the statistical median and percentages was applied.Results: we received 15 questionnaires: 10 complete, 5 incomplete. The incidence of MM since 2003 decreased by 20-50% for 42.9% and more than 80% for 21.4% of respondents. Of 413 postpartum surgeries, 72.8% were performed between 12-48 hours. 62 by fetal surgery, around week 28.5. The main complication was cerebral spinal fluid leak: 42.7% A total of 314 ventricle peritoneal shunts (VPS) were implanted, 81.7% from birth to 30 days. Symptomatic Chiari treated by occipitocervical decompression (OD): 73 cases, with two peaks, in the first month of life (27.6%) and 3-6 months (24.1%). 57.1% of known patients survived 20 years and more.Conclusion: flour fortification has decreased the incidence of MM. Closure during the 24 hours postpartum is the predominant behavior. Fetal surgery is not performed on a massive scale. Orthopedic surgery induces OD even in asymptomatic patients. Transitional medicine has been poorly implemented.
Keywords: Chiari; Folic acid; Spina bifida; Survival